(untitled) (Kinesiology, 2020)
The practice of long- and medium-distance races has exponentially increased the number of participants in recent years. They are carried out under extreme conditions that cause both biochemical and anthropometric changes in athletes and, in addition, have serious risks associated, such as dehydration, thermal disorders, or hypoglycemia. Knowledge regarding alterations at hematological level after this type of effort is limited. The objectives of this pre-post analytical descriptive observational study were: to describe and compare hematological values in amateur runners pre and post road marathon and ultratrail races, and to compare the hematological parameters between the groups in the two times analyzed by means of univariate descriptive statistical analyses, intra-group pre-post comparisons (Wilcoxon Signed-Rank Test), and comparisons between the groups (Mann-Whitney U Test). Effect size was calculated using Cohen’s D. An explanatory model (Multiple Logistic Regression) was created. Statistical significance was set at p<.05. The Wilcoxon test for marathon runners observed significant differences (p≤.001) in the white series. In ultratrail runners, the results were similar, with significant differences (p≤.001) in the platelet series. The Mann-Whitney U test showed the same pre-race hematological conditions for both groups, except for hematocrit and corpuscular values (p≤.001). Significant differences (p≤.001) were also found in the post-race leukocyte and neutrophil values. Significant differences in hematological parameters have been observed both between and within the groups. The differences with greater significance corresponded to the leukocyte series.